Development of Video Blogging Media (Vlog) in Geography Learning in Class XII Social Studies SMAN 1 Tilango Gorontalo Regency - Nur'ain Gani; Sri Maryati; Daud Yusuf (Universitas Lambung Mangkurat, 2023)
In this modern era, the development of learning media must be in accordance with technological developments. The results of observations and interviews at the research location show that the utilization of media in the learning process is still very lacking. Audio-visual media and electronic media have not been intensively utilized in learning. This research aims to develop video blogging (vlog) learning media in geography learning on the material of spatial interaction of rural and urban. This research is development research that applies the Research and Development (R&D) research method with the ADDIE approach.Â This research includes 5 stages, namely the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The validation results from media experts get a score of 77% (valid), material expert validation gets a percentage value of 92% (very valid), while validation by learning experts gets a score of 92.5% (very valid). Student responses from limited scale trials get a percentage of 84.7%, while student responses from general scale trials get a percentage of 89.6%. The conclusion of this research is that the developed video blogging-based learning media is suitable for use in the learning process.Development of Video Blogging Media (Vlog) in Geography Learning in Class XII Social Studies SMAN 1 Tilango Gorontalo Regency